2020
DOI: 10.1186/s12864-019-6376-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population genomics reveals genetic divergence and selection in lotus, Nelumbo nucifera

Abstract: Background: Lotus (Nelumbo nucifera) is an aquatic plant with important agronomic, horticulture, art and religion values. It was the basal eudicot species occupying a critical phylogenetic position in flowering plants. After the domestication for thousands of years, lotus has differentiated into three cultivated types-flower lotus, seed lotus and rhizome lotus. Although the phenotypic and genetic differentiations based on molecular markers have been reported, the variation on whole-genome level among the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
0
23
1
1
Order By: Relevance
“…SNP markers were frequently used in plant genetic diversity research, the construction of highdensity genetic linkage maps, and the identification of loci or genes related to complex traits (Chen et al, 2014;Winfield et al, 2016). A total of 107,133,072 SNPs and 141,866,26 insertions or deletions were detected, and most of these variants were located in intergenic regions or introns (Xanthopoulou et al, 2019;Li et al, 2020). The average dN/dS ratio of these Pyrus accessions was 1.044, and the numbers of synonymous SNPs exceeded the number of non-synonymous SNPs, similar to previous studies (Cheng et al, 2019;Li et al, 2019;Cui et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP markers were frequently used in plant genetic diversity research, the construction of highdensity genetic linkage maps, and the identification of loci or genes related to complex traits (Chen et al, 2014;Winfield et al, 2016). A total of 107,133,072 SNPs and 141,866,26 insertions or deletions were detected, and most of these variants were located in intergenic regions or introns (Xanthopoulou et al, 2019;Li et al, 2020). The average dN/dS ratio of these Pyrus accessions was 1.044, and the numbers of synonymous SNPs exceeded the number of non-synonymous SNPs, similar to previous studies (Cheng et al, 2019;Li et al, 2019;Cui et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With the continuing publication of the pear genome (Wu et al, 2013;Linsmith et al, 2019;Ou et al, 2019;Dong et al, 2020) and the rapid development of high-throughput sequencing technologies, it provided a foundation for a genome-wide variation analysis of germplasm resources and the functional gene mining, phylogenetic analysis, population genetic structure, genetic diversity, analyses and selective elimination (Zhou et al, 2020), which is of great significance for the study of molecular breeding and population evolution of species. Li et al (2020) used whole-genome resequencing to analyze the evolution and domestication characteristics of 69 lotus accessions founding that the flower lotus was biphyletic and genetically heterogeneous, whereas the rhizome and seed lotus were monophyletic and genetically homogeneous. Besides they identified a total of 1,346 selected regions in different lotus.…”
Section: Introductionmentioning
confidence: 99%
“…and flower lotus were admixed (Huang et al, 2018). Besides that, 69 lotus accessions (45 cultivated accessions, 22 wild sacred lotus accessions and two wild American lotus accessions) were resequenced, and the selective sweep regions contributed to the rhizome, flower and seed lotus were identified (Li et al, 2020). Owing to its unique characteristic, its basal position and diversity in plant evolutionary history, research into the origin and evolution of lotuses is important, a larger sample capacity of various cultivated lotuses for resequencing analysis was necessary to comprehensively investigate relative loci and genes of cultivated lotus domestication, which could have major application value for lotus breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Just a few genetic studies on lotus diversity have been reported, including a genetic map for large‐scale discovery of SNPs between cultivars of rhizome and seed lotuses, which was reported based on a ddRADseq library combined with NGS (Liu et al ., 2016) and 19 lotus individuals whole genome resequenced for genetic diversity and relationships with three cultivated temperate lotus (rhizome, seed and flower lotus) and wild lotus, which confirmed that wild lotus exhibited a higher genomic diversity than cultivated lotus, rhizome lotus had the lowest genomic diversity and closer relationship to wild lotus, but the seed and flower lotus were admixed (Huang et al ., 2018). Besides that, 69 lotus accessions (45 cultivated accessions, 22 wild sacred lotus accessions and two wild American lotus accessions) were resequenced, and the selective sweep regions contributed to the rhizome, flower and seed lotus were identified (Li et al ., 2020). Owing to its unique characteristic, its basal position and diversity in plant evolutionary history, research into the origin and evolution of lotuses is important, a larger sample capacity of various cultivated lotuses for resequencing analysis was necessary to comprehensively investigate relative loci and genes of cultivated lotus domestication, which could have major application value for lotus breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first draft genome assembly of the lotus variety China Antique was released 9 , many genomic studies have been carried out on lotus, such as whole-genome resequencing 7 , 10 , 11 , transcriptomic 12 14 , miRNA-based 15 17 and gene family studies 18 , 19 . The recent chromosome-level assembly of the China Antique genome facilitates genome-wide studies of functional genes and the evolution of lotus, but a web-based public database of lotus is still unavailable 8 .…”
Section: Background and Summarymentioning
confidence: 99%